2018
DOI: 10.2147/ott.s159337
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-647 promotes the therapeutic effectiveness of argon–helium cryoablation and inhibits cell proliferation through targeting TRAF2 via the NF-κB signaling pathway in non-small cell lung cancer

Abstract: BackgroundMicroRNA-647 (miR-647) has been reported to repress cell tumorigenic phenotype, while the function of miR-647 in non-small cell lung cancer was obscure.MethodsThe effect of miR-647 and TRAF2 on A549 and H1299 cells was explored through Methyl thiazolyl tetrazolium (MTT) assay, colony formation and cell cycle assays. Luciferase reporter assays, reverse transcription quantitative PCR (RT-qPCR) and Western blot assay were carried out to determine that TRAF2 is directly regulated by miR-647. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Moreover, we found that the cell invasion ability of glioma cells was suppressed by miR‐647 mimic. In summary, the results of the present study indicated that miR‐647 may function as a tumor suppressive role in glioma, which is consistent with its role in non‐small cell lung cancer or gastric cancer . A recent study reported that miR‐647 expression can be regulated by long non‐coding RNA PROX1‐AS1 and regulates gastric cancer progression and aggressiveness .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Moreover, we found that the cell invasion ability of glioma cells was suppressed by miR‐647 mimic. In summary, the results of the present study indicated that miR‐647 may function as a tumor suppressive role in glioma, which is consistent with its role in non‐small cell lung cancer or gastric cancer . A recent study reported that miR‐647 expression can be regulated by long non‐coding RNA PROX1‐AS1 and regulates gastric cancer progression and aggressiveness .…”
Section: Discussionsupporting
confidence: 88%
“…miR‐647 is reported to have a dual role in cancer progression in recent years. In non‐small cell lung cancer, Zhang et al . revealed that miR‐647 expression was significantly elevated in cancer tissues with argon‐helium cryoablation treatment compared to those without.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations